Pengaruh Persediaan Bahan Baku dan Pemeliharaan Mesin terhadap Hasil Produksi pada Konveksi I-Queen: Studi Kasus pada Konveksi I-queen di Tasikmalaya - Nanda Namira Ramadina; Suci Putri Lestari; Barin Barlian (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine and analyze the effect of raw material inventory and machine maintenance on production result. The research method used is the quantitative method and the data used is secondary data obtained directly through interviews with company owners. In this study, sampling used a periodic data approach with a semester scale of 20 samples. The variables used in this study are two independent variables and one dependent variable, so the most appropriate analysis tool is multiple linear regression. Based on the results of multiple linear analysis, it is known that the amount of raw material inventory and labor hours simultaneously and partially have a significant effect on production result. It can also be seen from the company's data that every increase in raw material inventory and machine maintenance result in a increase in productionthe. The calculation results show that there is a very strong relationship between the variable amount of raw material inventory and increasing production result.